A SAS-6-like protein suggests that the Toxoplasma conoid complex evolved from flagellar components - de Leon, Jessica, Cruz; Scheumann, Nicole; Beatty, Wandy; Beck, Josh R.; Tran, Johnson Q.; Yau, Candace; Bradley, Peter J.; Gull, Keith; Wickstead, Bill; Morrissette, Naomi S. (American Society for Microbiology, 2013)
SAS-6 is required for centriole biogenesis in diverse eukaryotes. Here, we describe a novel family of SAS-6-like (SAS6L) proteins that share an N-terminal domain with SAS-6 but lack coiled-coil tails. SAS6L proteins are found in a subset of eukaryotes that contain SAS-6, including diverse protozoa and green algae. In the apicomplexan parasite Toxoplasma gondii, SAS-6 localizes to the centriole but SAS6L is found above the conoid, an enigmatic tubulin-containing structure found at the apex of a subset of alveolate organisms. Loss of SAS6L causes reduced fitness in Toxoplasma. The Trypanosoma brucei homolog of SAS6L localizes to the basal-plate region, the site in the axoneme where the central-pair microtubules are nucleated. When endogenous SAS6L is overexpressed in Toxoplasma tachyzoites or Trypanosoma trypomastigotes, it forms prominent filaments that extend through the cell cytoplasm, indicating that it retains a capacity to form higher-order structures despite lacking a coiled-coil domain. We conclude that although SAS6L proteins share a conserved domain with SAS-6, they are a functionally distinct family that predates the last common ancestor of eukaryotes. Moreover, the distinct localization of the SAS6L protein in Trypanosoma and Toxoplasma adds weight to the hypothesis that the conoid complex evolved from flagellar components.